Health-related quality of life in post-stroke patients attended at tertiary-level hospitals in Bangladesh - Islam, Mohammad Jahirul; Ahmed, Sohel; Kakuli, Samena Akter; Rahman, Mohammad Habibur; Numan, Sharker Md.; Chakraborty, Shishir Ranjan; Uddin, Md. Jamal; Kader, Manzur (Frontiers in Stroke, 2024)
Background: Insufficient data on the health-related quality of life (HRQoL) of stroke survivors in less-resourced regions like Bangladesh emphasizes the need for understanding influencing factors. In this cross-sectional study, our objective was to assess potential factors associated with the HRQoL among stroke survivors in Bangladesh. Methods: The study included 424 stroke survivors (65% male, mean age 57.25±12.13 years) undergoing rehabilitation at four tertiary-level hospitals in Bangladesh. The HRQoL was assessed using the European Quality of Life Scale-5 Dimensions (EuroQol-5D), covering mobility, self-care, usual activities, pain/discomfort, and anxiety/depression, along with a visual analog scale (VAS). Sociodemographic (e.g., age, marital status, education) and health-related factors (e.g., type and duration of stroke, co-morbidity) served as independent variables. Bivariate logistic regression was utilized to ascertain the estimated risk factors for HRQOL, presenting odds ratios (OR) and a 95% confidence interval (CI) after adjusting for potential confounders. Results: Most participants resided in rural areas (57.8%) and had primary education (67.7%). Stroke survivors had a mean EQ summary index of 0.393 ± 0.46 and a VAS score of 40.43 ± 18. A significant portion experienced a stroke within 1-3 months (66%), with 52.6% reporting left-side weakness. Study findings show high prevalence of challenges: 79.5% mobility issues, 81.1% dependence in self-care, 87% activity limitations, 70.8% bodily pain, and 84% anxiety or depression symptoms. Widowed or single stroke survivors face higher difficulties in mobility (Adjusted OR, AOR=1.24, 95% CI=0.35–4.45) and pain/discomfort (AOR=2.85, 95% CI=0.85–9.27) compared to married survivors. Stroke survivors without rehabilitation services experience significantly higher difficulty levels: almost thirty times more in mobility (AOR=29.37, 95% CI=8.85–97.50), nearly forty-four times more in self-care (AOR=43.21, 95% CI=10.02–186.41), forty-four times more in usual activities (AOR=43.47, 95% CI=5.88–321.65), almost five times more in pain/discomfort (AOR=4.35, 95% CI=2.45–7.71), and more than twenty times more in anxiety/depression compared to those receiving rehabilitation services. Conclusion: The findings suggest that the enhancement of HRQoL in post-stroke patients in Bangladesh necessitates targeted interventions, including family support, tobacco cessation, recurrent stroke prevention, and effective rehabilitation services. Longitudinal studies are recommended for further confirmation of these findings